The Economics of Media Markets : A Literature Review - Ralf Dewenter (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
Media and especially mass media like newspapers or magazines are characterised by a number of peculiarities which are interesting from both a theoretical and empirical point of view.The interrelationship of reader and advertising markets,high sunk costs and large economies of scale are typical features.This paper reviews the existent literature on media markets and their peculiarities and lines out areas for further research.
urn:nbn:de:gbv:705-opus-1380
Keywords: 330; Medienökonomik; Zeitungsverlag; Zeitschriftenverlag; Theorie; Welt